2013
DOI: 10.1186/1742-4690-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Tim-3 expression on natural killer cells is associated with increased Galectin-9 levels in HIV-1 infection

Abstract: BackgroundNatural killer (NK) cells constitutively express high levels of Tim-3, an immunoregulatory molecule recently proposed to be a marker for mature and functional NK cells. Whether HIV-1 infection modulates the expression of Tim-3 on NK cells, or the levels of its ligand Galectin-9 (Gal-9), and how signaling through these molecules affects the NK cell response to HIV-1 remains inadequately understood.ResultsWe analyzed Tim-3 and Gal-9 expression in a cohort of 85 individuals with early and chronic HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 50 publications
4
62
0
Order By: Relevance
“…Although Tim-3 expression can actually delineate mature cytotoxic NK cells, its engagement results in suppression of cytotoxicity (33). Indeed, the ligand for Tim-3, Gal-9, is increased in HIV patients, and the continued exposure of Tim-3 ϩ NK cells to ligands leads to exhaustion and/or anergy (34), which could explain our observations. Recent reports specific to SIV-infected macaques indicate that Tim-3 also delineates exhausted T cells in SIV infection and that they accumulate in lymph nodes during disease (35).…”
Section: Resultsmentioning
confidence: 69%
“…Although Tim-3 expression can actually delineate mature cytotoxic NK cells, its engagement results in suppression of cytotoxicity (33). Indeed, the ligand for Tim-3, Gal-9, is increased in HIV patients, and the continued exposure of Tim-3 ϩ NK cells to ligands leads to exhaustion and/or anergy (34), which could explain our observations. Recent reports specific to SIV-infected macaques indicate that Tim-3 also delineates exhausted T cells in SIV infection and that they accumulate in lymph nodes during disease (35).…”
Section: Resultsmentioning
confidence: 69%
“…However, it is currently unknown if TIM-1 plays a role in HIV-1 replication and infection, although reduced TIM-3 expression on NK cells has been reported to be associated with chronic HIV-1 infection (18). Here we report that TIM-1 inhibits HIV-1 release, resulting in decreased virus production.…”
mentioning
confidence: 64%
“…79 The elevated Gal-9 level in ARV-suppressed subjects may be attributed to the presence of unspliced cellular HIV RNA. Soluble Gal-9 levels have been shown to be elevated in the plasma of HIV-infected subjects, [65][66][67] and Jost et al 66 have shown that despite ARV therapy, chronic HIV-infected adults did not experience declines in plasma Gal-9 levels when compared to untreated chronic HIV-infected subjects. Elite controllers maintaining a viral load of < 50 copies/ml represent less than 1% of all untreated HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…33,60,62,63 During chronic HIV infection, Gal-9-expressing Treg cells are presumed to selectively suppress the proliferation of nonprotective HIVspecific CD8 + T cells with high Tim-3 levels, but not protective HIV-specific CD8 + T cells with low levels of Tim-3. 64 Soluble Gal-9 levels have been shown to be elevated in the plasma of HIV-infected subjects, [64][65][66] suggesting that Gal-9 may play an important role in HIV pathogenesis. Engagement of Gal-9 with Tim-3 + CD4 + T cells in vitro renders CD4…”
Section: Introductionmentioning
confidence: 99%